Risk of early-onset prostate cancer associated with occupation in the Nordic countries. (December 2017) - Barry, Kathryn Hughes; Martinsen, Jan Ivar; Alavanja, Michael C.R.; Andreotti, Gabriella; Blair, Aaron; Hansen, Johnni; Kjærheim, Kristina; Koutros, Stella; Lynge, Elsebeth; Sparèn, Pär; Tryggvadottir, Laufey; Weiderpass, Elisabete; et al.
Abstract: Background: Early-onset prostate cancer is often more aggressive and may have a different aetiology than later-onset prostate cancer, but has been relatively little studied to date. We evaluated occupation in relation to early- and later-onset prostate cancer in a large pooled study. Methods: We used occupational information from census data in five Nordic countries from 1960 to 1990. We identified prostate cancer cases diagnosed from 1961 to 2005 by linkage of census information to national cancer registries and calculated standardised incidence ratios (SIRs) separately for men aged 30–49 and those aged 50 or older. We also conducted separate analyses by period of follow-up, 1961–1985 and 1986–2005, corresponding to pre- and post-prostate-specific antigen (PSA) screening. Results: For early-onset prostate cancer (n = 1521), we observed the highest SIRs for public safety workers (e.g. firefighters) (SIR = 1.71, 95% confidence interval [CI]: 1.23–2.31) and military personnel (SIR = 1.97, 95% CI: 1.31–2.85). These SIRs were significantly higher than the SIRs for later-onset disease (for public safety workers, SIR = 1.10, 95% CI: 1.07–1.14 and for military personnel, SIR = 1.09, 95% CI: 1.05–1.13; pheterogeneity = 0.005 and 0.002, respectively). Administrators and technical workers also demonstrated significantly increased risks for early-onset prostate cancer, but the SIRs did not differ from those of later-onset disease (pheterogeneity >0.05). While our early-onset finding for public safety workers was restricted to the post-PSA period, that for military personnel was restricted to the pre-PSA period. Conclusion: Our results suggest that occupational exposures, particularly for military personnel, may be associated with early-onset prostate cancer. Further evaluation is needed to explain these findings. Highlights: Public safety workers and military personnel had the highest standardised incidence ratios (SIRs) for early-onset prostate cancer (PCa). Elevated SIR for public safety workers persisted after removing firefighters. Administrators and technical workers also had elevated SIRs for early-onset PCa. Military early-onset finding was restricted to the pre-prostate-specific antigen period. Results provide clues about the aetiology of early-onset PCa, which is poorly understood.